Post-war Reconstruction - Conservation Strategies for the Local Architectural Identity of the Mosul house for the post war - Saeed, Marwa Mohamed; Hassan, Shorsh Salam (Sulaimani Journal for Engineering Sciences, 2019)
Humanity has witnessed in the past and continues to witness many devastating wars, which showed the weakness of the urban heritage in front of the destructive power of weapons and wars. With the disappearance of several archaeological buildings after the Second World War, the human being started to realize the importance of the local identity and worried about it from dissolution. This issue has emerged as a conflict that witnessed bloody wars and armed conflicts starting with the world war I and world war II, as well as many other civil wars that occurred in different countries in the world either for national or religious community divisions. Those wars have often led, at the cultural level, to a partial or entire destruction in the areas of conflict, the loot of heritage pieces and the burning of libraries. However, it is clear that the urbanized heritage is represented by the local heritage buildings, which are the product of human thought and culture and the conservation of the urban heritage has thus become a human historic responsibility. The importance of this research is represented for the urgent need to define the general guidelines for the reconstruction of Mosuli houses after the recent war. It is decided in order to create a local architectural identity that expresses the zeitgeist and achieves continuity with the heritage and local history of the city of Mosul, rich in heritage and history. So, this has created the research problem (Identifying strategies for redesigning and reconstruction the Mosuli house after Isis war). The research assumes that the application of local heritage elements will achieve a featured local identity for the houses to be reconstructed after the war. The aim of the research is to guide the strategies of re-implementation and reconstruction in order to preserve the local identity. To approach these goals, some experiences of other countries in the rehabilitation of cities after wars were mentioned, as well as some local architectural concepts related to post-war reconstruction were reviewed. Then, after that come up with a strategy that organizes reconstruction process. This study was mainly based on the analytical approach of several Mosuli houses to achieve the optimal strategy for the reconstruction of the Mosuli house post-war and also to obtain best possible outcomes regarding the local architectural identity of the city of Mosul.
Keywords: Conservation; Architectural Identity; Post-war Reconstruction; Mosul House